VERSO IL SISTEMA LOCALE TERRITORIALE DEL CIBO - Nadia Tecco; Marco Bagliani; Egidio Dansero; Cristiana Peano (Bollettino della Società Geografica Italiana)
In recent years multiple studies and insights have been published on food systems, which have seen the proposal of a plurality of paradigms for the analysis and planning of territorial food systems. The objective of this paper is to perform a reconnaissance and systematisation of different theoretical and operational approaches that encode the relationship between space and food system and that are, or could be, used for an urban or local food policy. To this end, starting from a more general and abstract idea on the spaces of food, in their general and metaphoric valences, we discuss in depth the main approaches to the spatial processing of the food system found in literature and in the experiences of urban food planning, thus considering their developments and reciprocal hybridisations. Finally, a theoretical and operational definition of local territorial food system territorial will be provided, as an assumption and at the same time as the outcome of the reasoning and action for an integrated project and a local food policy.